2022
DOI: 10.3390/biology11040513
|View full text |Cite
|
Sign up to set email alerts
|

Role of Betaglycan in TGF-β Signaling and Wound Healing in Human Endometriotic Epithelial Cells and in Endometriosis

Abstract: Endometriosis is characterized by the presence of ectopic endometrium most often in the pelvis. The transforming growth factor-beta (TGF-β) superfamily is also involved in the pathogenesis; however, betaglycan (BG, syn. TGF-β type III receptor) as an important co-receptor was not studied. We analyzed mainly BG ectodomain shedding because released soluble BG (sBG) often antagonizes TGF-β signaling. Furthermore, we studied the role of TGF-βs and BG in wound healing and evaluated the suitability of BG measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 62 publications
1
11
0
Order By: Relevance
“…Recently, we observed that BG is a vital modulator of TGF-β2 signaling in rat Sertoli cells [ 31 ] and that TGF-β1/2/3 modulate the shedding of BG in human endometrial cells [ 30 ]. In the current study, we demonstrated that activin A suppresses the shedding of BG in human endometriotic cells via the ALK-4/SMAD3 axis but, surprisingly, follistatin did not block activin A activity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, we observed that BG is a vital modulator of TGF-β2 signaling in rat Sertoli cells [ 31 ] and that TGF-β1/2/3 modulate the shedding of BG in human endometrial cells [ 30 ]. In the current study, we demonstrated that activin A suppresses the shedding of BG in human endometriotic cells via the ALK-4/SMAD3 axis but, surprisingly, follistatin did not block activin A activity.…”
Section: Discussionmentioning
confidence: 99%
“…Endometriotic 12Z cells (2 × 10 5 cells) were cultured in 6-well plates and serum-starved (1% FCS) for 24 h and treated in duplicates with activin A (25 and 50 ng/mL) for 2 h. RNA was isolated and real time qPCR was carried out. SiRNA transfection, RNA isolation and RT-qPCR procedures were performed as previously described [ 30 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…MMP-3, -7, -9, and-13 are associated with disease susceptibility in endometriosis [ 96 ]. TGF-β is involved in the enhancement of MMP-2 and -3 secretion [ 97 ]. LSR knockdown increased the expression levels of MMP-2, -9, -10, and -14 in Sawano cells [ 86 ].…”
Section: Pathophysiological Changes In Endometriosis and Endometrial ...mentioning
confidence: 99%